Greek Metaphysics and the Perspectives of Socrates, Plato and Aristotle in the Context of Physical Education - Patel, Shri Krishna; Srivastava , Sanjay; Prajapati, Manoj Kumar Prajapati (Integrated Journal for Research in Arts and Humanities, 2022)
Plato emphasized the importance of physical education for soul development in his book ‘Phaedo’, which Socrates shunned for the same reason. Plato emphasized the physical component and the harmonious balance of the material and spiritual in his books ‘Republic’ and ‘Laws’. In his book ‘Politics’, Aristotle defined three elements of excellent education, the first of which was physical health. In this framework, sports and physical education should take precedence.